L’irrigation avec des eaux usees et la sante: evaluer et attenuer les risques dans les pays a faible revenu. In French [Wastewater irrigation and health: assessing and mitigating risk in low-income countries] - Drechsel, Pay; Scott, Christopher A.; Raschid-Sally, Liqa; Redwood, M.; Bahri, Akissa (International Water Management Institute, 2011)
In most developing countries wastewater treatment systems have very low coverage or function poorly, resulting in large-scale water pollution and the use of poor-quality water for crop irrigation, especially in the vicinity of urban centres. This can pose significant risks to public health, particularly where crops are eaten raw.